Rancangan Sistem Monitoring Dan Pengaturan Energi Listrik Menggunakan Jaringan Internet Berbasis NODEMCU - M. Fiqri Haikal; Hamdani; Beni Satria (Jurnal Nasional Teknologi Komputer, 2026)
As more and more people use electricity, we need a good way to monitor how much energy is being used in real-time. The goal of this study is to create and implement a system that can monitor how much power is being used in a room. The system will use a NodeMCU microcontroller and a YHDC SCT-013-000 current sensor, and the MQTT protocol will be used to send data. Current sensors measure the electric current in the power source. The NodeMCU then processes this information and sends it via WiFi to the server, where it is displayed on the monitoring application. This study uses hardware design, software design, and system testing methodologies to assess the performance and accuracy of the sensors used. When the device is turned off, the YHDC SCT-013-000 current sensor can read the electric current with a difference of 0.03 Amper. When the device is turned on, it can detect a current with a difference of 0.17 Amperes compared to a clamp multimeter. The system also connects to a WiFi network and provides data to the server using the MQTT protocol. This makes it possible to see how much electricity is being used in real-time through websites and apps. So, the built system can be used to monitor how much electricity is consumed in an easier, more efficient, and more useful way